FAKTOR-FAKTOR PENYEBAB KERUSAKAN DOKUMEN REKAM MEDIS RAWAT JALAN DI RUANG PENYIMPANAN RUMAH SAKIT ISLAM SITI KHADIJAH PALEMBANG : Lely Meriaya Sari (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
The duties, roles and functions of the filing are the filing section serves as a security guard and confidentiality of medical record documents, protects medical record documents from the dangers of physical, chemical, biological damage, assists in the assessment of value for medical records, assists in the implementation of the destruction of medical record forms. This type of research is descriptive research with a qualitative approach. The population in this study was the entire outpatient medical record file in March in the storage room of Siti Khadijah Palembang Islamic Hospital in 2021 and the sample was chosen by using random sampling. The data collection techniques in this study are observations, interviews, documentation and checklists. The study results obtained damage to medical record documents in the storage room RSI Siti Khadijah Palembang by 15%. Intrinsic factors that include the quality of paper, maps, ink, and adhesives are mostly in good condition so it is less likely to be a factor causing damage. Extrinsic factors include dust. It is recommended that rsi Islam Siti Khadijah Palembang add facilities in the storage room, such as installing temperature gauges and humidity temperature in the storage room